Lung function response and side effects to rapamycin for lymphangioleiomyomatosis: a prospective national cohort study - Bee, Janet; Fuller, Sharon; Miller, Suzanne; Johnson, Simon R. (BMJ Publishing Group, 2017)
Rationale